ANÁLISE DOS PROCEDIMENTOS DE COTAÇÃO DE PREÇOS NAS COMPRAS PÚBLICAS NA UNIDADE DE ALEGRE DA UFES - Oliveira, Janaina Tavares Noleto de (2020)
As an introduction, the importance and difficulties encountered in public procurement processes are highlighted here, in which it is necessary to insert standardized procedures in bidding processes, so that the procedures are more efficient. Thus, one of